Angiography‐guided mid/high septal implantation of ventricular leads in patients with congenital heart disease. Issue 6 (17th September 2021) - Shenthar, Jayaprakash; Valappil, Sanjai P.; Rai, Maneesh K.; Banavalikar, Bharatraj; Padmanabhan, Deepak; Delhaas, Tammo
Abstract: Background: Conduction system pacing prevents pacing‐induced cardiomyopathy, but it can be challenging to perform in patients with congenital heart disease (CHD), and mid/high septal lead implantation is an alternative. This study aimed to assess intraprocedural angiography's utility as a guide for mid/high‐septal lead implantation in CHD patients. Methods: The study subjects were CHD patients with Class I/IIa indications for permanent pacemaker implantation. To guide septal lead implantation, we performed an intraprocedural right ventricular angiogram in anteroposterior, 40° left anterior oblique, and 30° right anterior oblique. The primary endpoint was the lead tip in the mid/high septum on computed tomography (CT). The secondary endpoints were complications and systemic ventricular function on follow‐up. Results: From January 2008 to December 2018, we enrolled 27 patients (mean age: 30 ± 20 years; M:F 17:10) with CHD (unoperated: 20, operated: 7). The mean paced QRS duration was 131.7 ± 5.8 ms, and CT done in 22/27 patients confirmed the lead tip in the mid‐septum in 16, high septum in 5, and apical septum in 1 patient. There were no procedural complications, and during a mean follow‐up of 58 ± 35.2 months, there was no significant change in the systemic ventricular ejection fraction (56.4 ± 8.3% vs 53.9 + 5.9%, P = .08). Two patients with Eisenmenger syndrome died because of refractory heart failure. Conclusions: Intraprocedural angiography is safe and useful to guide mid/high‐septal lead implantation in CHD patients. Mid/high septal lead position preserves systemic ventricular function in patients with CHD during medium‐term follow‐up. Abstract : Mid/high septal pacing can be an alternative to right ventricular apical pacing to avoid pacing induced cardiomyopathy. Intraprocedural angiography during permanent pacemaker implantation can define the altered septal anatomy in real time to guide mid/high septal lead placement. Mid/high septal lead placement preserves systemic ventricular function in medium term and is safe mid/high septal lead placement. Mid/high septal lead placement preserves systemic ventricular function in medium‐term and is safe.